2021
DOI: 10.1038/s41531-021-00259-7
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein aggregation in the olfactory bulb induces olfactory deficits by perturbing granule cells and granular–mitral synaptic transmission

Abstract: Olfactory dysfunction is an early pre-motor symptom of Parkinson’s disease (PD) but the neural mechanisms underlying this dysfunction remain largely unknown. Aggregation of α-synuclein is observed in the olfactory bulb (OB) during the early stages of PD, indicating a relationship between α-synuclein pathology and hyposmia. Here we investigate whether and how α-synuclein aggregates modulate neural activity in the OB at the single-cell and synaptic levels. We induced α-synuclein aggregation specifically in the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 63 publications
8
42
0
Order By: Relevance
“…Our electrophysiological results revealed that mitral cells with impaired inhibitory synaptic transmission exhibited higher cluster discharge activity. The increased firing activity of mitral cells induced by Meth is consistent with the result of direct injection of α-syn into the olfactory bulb ( Chen et al, 2021 ), and similar damage to the inhibitory regulation of mitral cells has also been found in other neurodegenerative diseases, such as Alzheimer’s disease (AD) ( Hu et al, 2021 ). Parallel to the results, the inhibitory synaptic transmission manifested by inhibitory postsynaptic currents (IPSCs) was impaired, thus impairing local inhibitory circuits.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Our electrophysiological results revealed that mitral cells with impaired inhibitory synaptic transmission exhibited higher cluster discharge activity. The increased firing activity of mitral cells induced by Meth is consistent with the result of direct injection of α-syn into the olfactory bulb ( Chen et al, 2021 ), and similar damage to the inhibitory regulation of mitral cells has also been found in other neurodegenerative diseases, such as Alzheimer’s disease (AD) ( Hu et al, 2021 ). Parallel to the results, the inhibitory synaptic transmission manifested by inhibitory postsynaptic currents (IPSCs) was impaired, thus impairing local inhibitory circuits.…”
Section: Discussionsupporting
confidence: 70%
“…Normal neural activity and synaptic plasticity of mitral cells are required for the efficient performance of olfactory function, and the accumulation of α-syn is tightly coupled with abnormal electrical activity of olfactory neurons ( Chen et al, 2021 ). According to the cell-attached recordings, Meth increased the spontaneous firing rate of mitral cells; this effect could be alleviated by exercise but blocked upon α-syn restoration ( Figures 6A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence from our lab and others links similar disruption in patterns of network oscillations to prodromal symptoms, using the early anatomical target—the olfactory system. 188 , 189 An advantage of using the olfactory system is that the sensory information is monosynaptically conveyed from the OB into down-stream cortices. α-Syn aggregate formation in the OB results in olfactory perceptual dysfunction.…”
Section: Mechanisms Underlying Early Network Dysfunction: What We Kno...mentioning
confidence: 99%